Discovery of natural scaffolds as HER2 inhibitors for breast cancer: virtual screening, molecular dynamics, and biological characterization with selectivity profiling - Asmaa Hossam; Ingy I. Abdallah; Nadia A. El-Sebakhy; Radwan Alnajjar; Mohamed M. Mohyeldin (Scientific Reports)
Abstract Nature offers potential therapeutic candidates for breast cancer (BC), and targeting HER2 signaling presents a promising approach, leveraging the successful history of anticancer drug discovery. Using a structure-based virtual screening workflow, a comprehensive library of natural products (NPs) was screened for potential HER2 binding. Five of these NPs were selected for in-depth biological validation against BC. Biochemically, oroxin B, liquiritin, ligustroflavone, and mulberroside A suppressed HER2 catalysis with nanomolar potency. Binding mode studies of NPs revealed their binding patterns, providing valuable SAR insights for effective HER2 inhibition. Further cellular assays revealed that the top NPs have preferential anti-proliferative effects towards HER2 over-expressing BC cells, with notable selectivity indices. Liquiritin exhibited promising anti-migratory activity in two cellular motility models, while other tested hits primarily inhibited cancer cell growth with minimal effects on metastasis. Liquiritin and oroxin B stood out as validated hits, revealing the most promising profiles. ADME predictions and MD simulations positioned liquiritin as a more promising HER2 inhibitor than oroxin B, despite oroxin B’s higher ranking in rigid docking studies. On the molecular level, liquiritin significantly inhibited HER2 phosphorylation and expression in BC cells. Liquiritin demonstrated notable selectivity for HER family proteins when tested against various kinases, highlighting its potential as a pan-HER inhibitor hit for future development. Further in vivo assessment is necessary to support the hit-to-lead promotion of liquiritin.